Pengaruh Konsentrasi Asam Stearat Terhadap Mutu Fisik Losion Ekstrak Daun Nangka (Arthocarpus heterophyllus) Sebagai Antioksidan - Sava Agasta, Natasya; Aisiyah, Siti; Ponco Rahayu, Mamik (Jurnal Farmasi (Journal of Pharmacy), 2022)
Jackfruit leaf extract was developed into a lotion preparation to increase skin moisture and prevent the skin from being exposed to free radicals. The purpose of this study was to determine the effect of variations in stearic acid base on physical quality, differences in antioxidant activity in jackfruit leaf extract and preparations, best formula that can provide antioxidant activity. Jackfruit leaf extract was obtained by maceration using 70% ethanol and then formulated with a concentration of 6% jackfruit leaf extract and variations in stearic acid base 2%, 3%, and 4%. This study used the DPPH method to determine antioxidant activity and ANOVA for statistical analysis. This study obtained the IC50 value of jackfruit leaf extract of 64.5616 ppm. The IC50 value of jackfruit leaf extract and lotion was different due to the presence of additional ingredients in the lotion. The best formula from this research, formula has the best physical quality value, with the IC50 value of the extract in the formula 70.6862 ppm and the IC50 value of the base in the formula 1179.3357 ppm.